Surgical site infections – an updated review of guidelines in the light of new scientific data - Lechowski, Sebastian; Kułakowska, Aleksandra; Kłakowicz, Philip; Lepczyński, Bartłomiej; Siedlak, Agnieszka (Journal of Education, Health and Sport, 2023)
Surgical site infections are important and still more growing burden in 2023. WHO estimated that SSIs are one of the most common and frequent healthcare associated infections (HAI), and in the world’s perspective, it can occur up to 10% after surgeries [1]. The knowledge about preliminary and novel ways of diagnosis and treatment and prevention of this disease are important in improving outcomes. Reducing the amount of complications after surgeries is crucial in helping with the recovery and it is an outcome of both proper prehabilitation and safe surgical protocols . Especially focus on the preventive measures for SSI, early diagnosis and aggressive treatment can really improve overall survival, lower the incidence of further complications (including sepsis), and improve patients recovery. This paper summarizes the current guidelines indications as well as their reflection in novel published data.